Air foil Shape Optimization Using Cfd And Parametrization Methods. (2018) - Anitha, D.; Shamili, G.K.; Ravi Kumar, P.; Sabari Vihar, R.
Abstract: The efficient aerodynamic performance is carried out by selection of wing airfoil. The optimal shape of the airfoil generates high lift and low drag within the design constraints often imposed by the structural requirements. In the present study, the optimization of airfoil shape is carried out using genetic algorithm, particle swarm optimization methods for a typical airfoil NACA4412 in MATLAB environment. Airfoil parameterization is done using cubic spline, PARSEC and CST methods. Panel method based flow solver XFOIL is used as flow solver for optimization. Flow simulation of airfoil is also carried out on CFD software ANSYS FLUENT. The optimization is carried out for maximum lift and minimum drag.